괴사성 장염의 수술 경험 - 남소현(So-Hyun Nam); 김대연(Dae-Yeon Kim); 김성철(Seong-Chul Kim); 김인구(In-Koo Kim) (Annals of surgical treatment and research, 2009)
Purpose: Necrotizing enterocolitis (NEC) is a severe inflammatory disorder of the intestine, causing high mortality and morbidity. We investigated the single center experience about the operative indication, treatment method, and mortality in NEC. Methods: The medical records of infants (＜1 year old) who underwent the operation due to complications of NEC at the Asan Medical Center from Jan 1997 to Dec 2007 were retrospectively reviewed. Results: Among 49 patients (M：F = 34：15), 37 underwent the operation at acute phase of NEC, average 26.43± 35.43 days after birth (3∼168), due to pneumoperitoneum in 23, clinical deterioration in 12 and abdominal mass in 2. Average gestational age was 234.64±38.27 days (161∼279) and birth weight was 2,061.38±999.49 g (563∼3,740). The extent of necrosis was classified grossly as focal in 14 cases, multifocal in 14 and panintestinal in 9 and the operative methods were enterostomy in 30 patients, resection and anastomosis in 6 and open drainage in 1. Thirteen patients (35.1%) were expired - 8 (21.6%) died of necrotizing enterocolitis and 5 died of other causes. The other 12 patients underwent operation for stricture after NEC at average 81.17±77.22 days after birth (32∼317). Average gestational age was 240.83±34.4 days (173∼280) and birth weight was 2,089.83±862.47 g (710∼3,200). Eight patients underwent resection and anastomosis including stricture and 4 patients underwent enterostomy. Conclusion: Resection and enterostomy was the preferred procedure but resection and anastomosis did not increase morbidity or mortality. Quite a number of patients suffered from the stricture after NEC. KCI Citation Count: 0